2006
DOI: 10.1158/0008-5472.can-05-2013
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Insulin-Like Growth Factor Binding Protein-3 Induces Apoptosis and Is Targeted to Ubiquitin/Proteasome–Dependent Proteolysis

Abstract: Insulin-like growth factor binding protein-3 (IGFBP-3), the product of a tumor suppressor target gene, can modulate cell proliferation and apoptosis by IGF-I-dependent and IGF-Iindependent mechanisms. IGFBP-3 controls the bioavailability of IGFs in the extracellular environment and is known to be subject to degradation by various extracellular proteases. Although nuclear localization and functions of IGFBP-3 have been described in the past, we show as the novel features of this study that the abundance of nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 40 publications
(48 reference statements)
4
53
0
Order By: Relevance
“…Apoptotic cells were detected according to Nicoletti et al 23 or by Annexin V staining 22 and counted by flow cytometry using a Becton Dickinson FACSCalibur and CellQuest software.…”
Section: Apoptosis Assaysmentioning
confidence: 99%
“…Apoptotic cells were detected according to Nicoletti et al 23 or by Annexin V staining 22 and counted by flow cytometry using a Becton Dickinson FACSCalibur and CellQuest software.…”
Section: Apoptosis Assaysmentioning
confidence: 99%
“…Most major IGFBPs have both IGFdependent and independent actions, the former exerted by binding and sequestering IGF and the latter by binding directly to cell membrane and nuclear receptors. IGFBP-3, in particular, displays antiproliferative effects and pro-apoptotic effects both through and independently of the p53 downstream pathway [Buckbinder et al 1995;Butt et al 2000;Devi et al 2000;Santer et al 2006;Kim et al 2004]. Levels of serum IGFBPs appear to be prognostic in NSCLC patients whether they are treated with an epidermal growth factor receptor (EGFR) tyrosine kinase receptor (TKI) drug or systemic chemotherapy [Fidler et al 2009;Karmali et al 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Most recent studies have suggested that ubiquitinproteasome-dependent proteolysis is also involved in apoptosis, although its precise role is controversial (7). Inhibitors of the proteasome can act through multiple mechanisms to arrest tumor growth, tumor spreading and angiogenesis.…”
Section: Introductionmentioning
confidence: 99%